2015
DOI: 10.1097/01.asw.0000470155.29821.ed
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Study of Innovative Spray Formulation Containing Ozonated Oil and α-Bisabolol in the Topical Treatment of Chronic Venous Leg Ulcers

Abstract: The innovative spray formulation of ozonated oil and α-bisabolol combination shows promise as an important new therapeutic option in the adjuvant treatment of venous ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 19 publications
0
77
0
5
Order By: Relevance
“…Marfella et al demonstrated a 50% decrease in biochemical markers that prevent healing with ozone compared with 7% in the control group. Four studies focused on the amount of ulcer closure and general appearance of the wound; these studies found a 24%, 50%, and 25% difference in favour of the ozone treatment. Zang et al found that ozone increased closure of ulcers by an average of 3.65 cm 2 compared with the control.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Marfella et al demonstrated a 50% decrease in biochemical markers that prevent healing with ozone compared with 7% in the control group. Four studies focused on the amount of ulcer closure and general appearance of the wound; these studies found a 24%, 50%, and 25% difference in favour of the ozone treatment. Zang et al found that ozone increased closure of ulcers by an average of 3.65 cm 2 compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…One study blew an oxygen‐ozone mixture directly into the cavity using a catheter and found an 85% wound closure rate compared with the 71% in the control group ( P = .05) . Of the 2 studies that used ozonised oil as a treatment method, Campanati et al demonstrated a significant ( P = .003) improvement in wound healing compared with the control, and Solovăstru. 2015 25% wound closures compared with the control, and the results were also statistically significant ( P = .05) (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations